From starburst to quiescence: post-starburst galaxies and their large-scale clustering over cosmic time. Issue 3 (15th April 2021) - Wilkinson, Aaron; Almaini, Omar; Wild, Vivienne; Maltby, David; Hartley, William G; Simpson, Chris; Rowlands, Kate
ABSTRACT: We present the first study of the large-scale clustering of post-starburst (PSB) galaxies in the high-redshift Universe (0.5 < z < 3.0). We select ∼4000 PSB galaxies photometrically, the largest high-redshift sample of this kind, from two deep large-scale near-infrared surveys: the UKIDSS Ultra Deep Survey Data Release 11 and the Cosmic Evolution Survey. Using angular cross-correlation techniques, we estimate the halo masses for this large sample of PSB galaxies and compare them with quiescent and star-forming galaxies selected in the same fields. We find that low-mass, low-redshift (0.5 < z < 1.0) PSB galaxies preferentially reside in very high mass dark matter haloes ( M halo > 10 14  M⊙ ), suggesting that they are likely to be infalling satellite galaxies in cluster-like environments. High-mass PSB galaxies are more weakly clustered at low redshifts, but they reside in higher mass haloes with increasing look-back time, suggesting strong redshift-dependent halo downsizing. These key results are consistent with previous results, suggesting that two main channels are responsible for the rapid quenching of galaxies. While high-redshift ( z > 1) galaxies appear to be quenched by secular feedback mechanisms, processes associated with dense environments are likely to be the key driver of rapid quenching in the low-redshift Universe ( z < 1). Finally, we show that the clustering of photometrically selected PSBs is consistent with them being direct descendants of highly dust-enshrouded submillimetre galaxies, providing tantalizing evidence for the oft-speculated evolutionary pathway from starburst to quiescence.